IDENTIFICATION OF POTENTIAL AND UTILIZATION OF NTFPs IN TAMAN HUTAN RAYA (TAHURA) SULTAN SYARIF HASYIM MINAS REGENCY RIAU PROVINCE - Asri Gumilar; Defri Yoza; Evi Sribudiani (Fakultas Pertanian, Universitas Riau, 2022)
This study aims to determine the potential and utilization of Non-Timber Forest Products (NTFPs) in TAHURA sultan syarif hasyim, Minas District, Riau Province. The research method is a survey method, with objects of forest area and the community around the forest. The data taken is primary data, namely the type of vegetation that has the potential to produce NTFPs and respondent profile data as well as their interest and to develop NTFPs. While secondary data in the form of conditions Tahura sultan syarif hasyim, Minas District, Riau Province and other supporting data. The results of all data were analyzed descriptively qualitatively. Interviews and answers to questionnaires from communities around the forest found 21 types of NTFPs that were utilized by the community. Only 18 respondents were aware of the potential of NTFPs, out of a total of 35 respondents. 21 types of NTFPs are utilized with various functions and benefits, such as food, medicine, and industrial raw materials. It can be concluded that the potential of NTFPs in the Minas Tahura Model KPHP is 21 species with different levels of diversity and dominance as well as different benefits and utilization of NTFPs utilized by communities around Tahura, namely wood, rattan, honey, fruits and resin resin.